A Synchronous Strategy to Zn-Iodine Battery by Polycationic Long-Chain Molecules - Cai, Da‑Qian; Xu, Hengyue; Xue, Tong; Yang, Jin‑Lin; Fan, Hong Jin (Nano-Micro Letters, 2025)
Aqueous Zn-iodine batteries (ZIBs) face the formidable challenges towards practical implementation, including metal corrosion and rampant dendrite growth on the Zn anode side, and shuttle effect of polyiodide species from the cathode side. These challenges lead to poor cycle stability and severe self-discharge. From the fabrication and cost point of view, it is technologically more viable to deploy electrolyte engineering than electrode protection strategies. More importantly, a synchronous method for modulation of both cathode and anode is pivotal, which has been often neglected in prior studies. In this work, cationic poly(allylamine hydrochloride) (Pah+) is adopted as a low-cost dual-function electrolyte additive for ZIBs. We elaborate the synchronous effect by Pah+ in stabilizing Zn anode and immobilizing polyiodide anions. The fabricated Zn-iodine coin cell with Pah+ (ZnI2 loading: 25 mg cm−2) stably cycles 1000 times at 1 C, and a single-layered 3 × 4 cm2 pouch cell (N/P ratio 1.5) with the same mass loading cycles over 300 times with insignificant capacity decay. Highlights: 1 A long chain polycation (Pah⁺) is propos ed to simultaneously regulate Zn anode deposition , mitigate side reactions and stabilize iodine cathode chemistry. 2 The iodophilic and low diffusivity nature of Pah enables effective polyiodide immobilization, suppressing the shuttle effect and ensuring a stable redox environment. 3 The Zn iodine battery delivers high areal capacity ( 4 mAh cm−2 at 1 C) and excellent durability, with 95% capacity retained over 1000 cycles.